A novel microduplication of ARID1B: Clinical, genetic, and proteomic findings. Issue 9 (10th July 2017) - Seabra, Catarina M.; Szoko, Nicholas; Erdin, Serkan; Ragavendran, Ashok; Stortchevoi, Alexei; Maciel, Patrícia; Lundberg, Kathleen; Schlatzer, Daniela; Smith, Janice; Talkowski, Michael E.; Gusella, James F.; Natowicz, Marvin R.
Abstract : Genetic alterations of ARID1B have been recently recognized as one of the most common mendelian causes of intellectual disability and are associated with both syndromic and non‐syndromic phenotypes. The ARID1B protein, a subunit of the chromatin remodeling complex SWI/SNF‐A, is involved in the regulation of transcription and multiple downstream cellular processes. We report here the clinical, genetic, and proteomic phenotypes of an individual with a unique apparent de novo mutation of ARID1B due to an intragenic duplication. His neurodevelopmental phenotype includes a severe speech/language disorder with full scale IQ scores 78–98 and scattered academic skill levels, expanding the phenotypic spectrum of ARID1B mutations. Haploinsufficiency of ARID1B was determined both by RNA sequencing and quantitative RT‐PCR. Fluorescence in situ hybridization analysis supported an intragenic localization of the ARID1B copy number gain. Principal component analysis revealed marked differentiation of the subject's lymphoblast proteome from that of controls. Of 3426 proteins quantified, 1014 were significantly up‐ or down‐regulated compared to controls ( q  < 0.01). Pathway analysis revealed highly significant enrichment for canonical pathways of EIF2 and EIF4 signaling, protein ubiquitination, tRNA charging and chromosomal replication, among others. Network analyses revealed down‐regulation of: (1) intracellular components involved in organization of membranes, organelles, and vesicles; (2) aspects of cell cycle control, signal transduction, and nuclear protein export; (3) ubiquitination and proteosomal function; and (4) aspects of mRNA synthesis/splicing. Further studies are needed to determine the detailed molecular and cellular mechanisms by which constitutional haploinsufficiency of ARID1B causes syndromic and non‐syndromic developmental disabilities.